Factor that affects the eagerness to perform pilgrimage of Umrah and Hajj / Anith Nabila Azhar...[et al.] - Azhar, Anith Nabila; Ridzuan, Abdul Rauf; Bakar, Mohd Hilmi; Sultan Mohideen, Rosilawati; Ilyas, Ilya Yasnoriza; Suyurno, S Salahudin (Faculty of Communication & Media Studies, 2020)
Saudi Arabia is an Arabic country in the Middle East. It is not only considered the homeland of the Arab people - it is thought that the first Arabs originated on the Arabian Peninsula - but also the homeland of Islam, the world's second-largest religion. It is the location of the two holy pilgrimage cities of Mecca and Medina. Due to the fact that Saudi Arabia has these two most sacred cities to Muslims, it is known for being one of the most conservative countries in the world. All Saudis are Arab Muslim. Arabic is the official language of the country, but English is considered to be a second language taught at schools and used in business. It is essential to realize that Islamic culture, which permeates every aspect of a Muslim's life, also permeates every aspect of the Saudi Arabian state (Bogari, 2002).